Clinical and morphological features and the assessment of survival in patients with iris melanoma - S. V. Saakyan; I. V. Svirina; A. Yu. Tsygankov; A. A. Zharov; N. S. Izmailova (Российский офтальмологический журнал)
Purpose. To analyze how the clinical and morphological features are associated with vital prognosis of iris melanoma patients.Material and methods. A retrospective analysis included 84 patients (54 women and 30 men) with iris melanoma treated between 2005 and 2019.The mean age at the time of treatment was 52.3 ± 14.5 years. All patients underwent standard and special ophthalmological examination, including ultrasound biomicroscopy, and followed up for 32 to 196 months (103.1 ± 44 months) after hospital discharge.Results. Pigmented tumors predominated (72.6% of patients), while others showed a slightly pigmented (15.4%) and nonpigmented forms (12.0%). Most of the patients (67.9%) received an organ preserving treatment, while others (32.1%) had to have a liquidating treatment (enucleation) due to anular tumor growth and secondary complications. Uveal melanoma was morphologically verified in all cases: spindle cell type A (14.3%), spindle cell type B (31.0%), mixed cell (42.8%), epithelioid cell (11.9%). The epithelioid cell type of tumor was more common when the tumor spread to the ciliary body rather than in iris melanoma (p = 0,046), but the spindle cell and mixed cell types were more common than the epithelioid cell type in both groups. An anular growth was typical for the epithelioid cell type of tumor (p = 0.006). The presence of vessels in tumor stroma was found to be more frequent in pigmented (p = 0.005) and non-pigmented forms (p = 0.0009). For pigmented tumors, spreading into the ciliary body was characteristic (p = 0.024).Conclusion. A retrospective analysis of clinical and morphological factors of iris melanoma patients with an iridociliary localization should that the specific survival was 98.8%, and overall survival was 87%. The data obtained indicated the importance of timely diagnosis of iris tumors for an organ preservation treatment.